Perancangan Alat Presensi Berdasarkan Pengenalan Wajah - Fawzi, Ahmad; Fat, Joni; Wulandari, Meirista (Universitas Tarumanagara, 2023)
: The attendance system is something that is commonly encountered every day by employees or students. A attendance that is neatly arranged certainly makes it easier when carrying out the data collection process. The attendance that is used to minimize abuse is by using a non-contact attendance. This attendance system utilizes one of the technologies from computer vision. Attendance system designed to apply digital image processing technology. Image processing is a method used to process or process from the original image so as to produce another image that suits your needs. The tool is designed to consist of several modules, namely the image acquisition module, processing module, information display module, and storage module. The image acquisition module used is a Logitech C920 webcam; a processing module is a Raspberry Pi 4B; an information display module is a 7-Inch Capacitive Touch Screen LCD, and a storage module is a 64GB SanDisk microSD. The attendance tool matches the facial image with the data that has been entered into the storage system. The algorithm for the face recognition method uses the Histogram of Oriented Gradients (HOG). Attendance data recording uses CSV format which consists of date, time of entry, time of exit, and subject name. Tests were carried out with several sample cases and tests with five different subjects. Each subject was subjected to a attendance experiment five times with a distance of ± 40 cm. The algorithm can recognize the subject accurately if the subject is facing right in the image acquisition module ABSTRAK: Sistem presensi merupakan hal yang biasa ditemui setiap harinya oleh pegawai ataupun pelajar/mahasiswa. Presensi yang tersusun secara rapi tentunya memudahkan saat dilakukan proses pendataan. Presensi yang digunakan untuk meminimalisir penyalahgunaan yaitu dengan menggunakan presensi non-kontak. Sistem presensi ini memanfaatkan salah satu teknologi dari computer vision. Sistem presensi yang dirancang menerapkan teknologi pengolahan citra digital. Pengolahan citra merupakan metode yang digunakan untuk mengolah ataupun memproses dari gambar asli sehingga menghasilkan gambar lain yang sesuai dengan kebutuhan. Alat yang dirancang terdiri beberapa modul yaitu modul akuisisi citra, modul pemroses, modul penampil informasi, dan modul penyimpanan. Modul akuisisi citra yang digunakan berupa webcam Logitech C920, modul pemroses berupa Raspberry Pi 4B, modul penampil informasi berupa LCD 7 Inch Capacitive Touch Screen, dan modul penyimpanan berupa microSD SanDisk 64 GB. Alat presensi mencocokkan gambar wajah dengan data yang telah dimasukkan ke dalam sistem penyimpanan. Algoritma untuk metode pengenalan wajah menggunakan Histogram of Oriented Gradients (HOG). Pencatatan data presensi menggunakan format CSV yang terdiri dari tanggal, waktu masuk, waktu keluar, dan nama subjek. Pengujian dilakukan dengan beberapa contoh kasus dan pengujian dengan lima subjek berbeda. Masing-masing subjek dilakukan percobaan presensi sebanyak lima kali dengan jarak ± 40 cm . Algoritma dapat mengenali subjek secara akurat jika subjek menghadap ke depan tepat pada modul akusisisi citra